The Position Of Human Rights in Indonesia Constitutional Law - Bahrain, Bahrain; Susanto, Deny; Darodjat , Tubagus Achmad (Journal Evidence Of Law, 2024)
This study aims to evaluate the position of human rights in Indonesian constitutional law, as well as identify challenges and solutions in the implementation of human rights protection based on the provisions in the 1945 Constitution of the Republic of Indonesia and related laws and regulations. The method used is normative research with a qualitative descriptive approach, which focuses on analysing primary, secondary, and tertiary legal materials. The results show that although Indonesia has regulated human rights constitutionally, the implementation of its protection is still constrained by the weakness of law enforcement institutions, limited resources, and political dynamics. In addition, state institutions that play a role in handling human rights violations such as the National Human Rights Commission and the Human Rights Court have limited authority that reduces their effectiveness. This study suggests that law enforcement agencies be strengthened and given greater authority to deal with human rights violations, as well as the importance of increasing public awareness and legal apparatus regarding the importance of human rights protection.